Methane degradation in biotrickling filters: Recyclable materials as a support medium - Gómez-Herrera, Santiago; Córdoba-Díaz, Yuly Alexandra; Morales-Pabón, Diana Carolina; Santacruz-Salas, Angie Paola; Leonel , Hugo Ferney (Revista de Ciencias Agrícolas, 2025)
Biofiltration is an alternative method for reducing methane, a greenhouse gas with public health risks and climate impacts. However, its feasibility is often limited by the high costs of organic beds and inadequate surface area. This study evaluated the removal efficiency and specific methane removal capacity of biotrickling filters (BTFs). In the air quality laboratory of the Universidad de Nariño, methane was diluted to a concentration of 4% in two BTFs with recycled material (polyethylene terephthalate - BTF1 and expanded polystyrene - BTF2) and inoculated with a methanotrophic microbial consortium. The reactors were operated in parallel for 24 hours per day with countercurrent flow under controlled conditions (25°C, 10 psi, neutral pH), TRLV of 31 min, and a flow rate of 6 L h-1 with a concentration of 2000 ppmv. BTF1 achieved a maximum removal efficiency (RE) of 75%, higher than BTF2’s 60%, likely due to the greater external specific area of PET. BTF1 and BTF2 showed a positive influence of temperature and humidity on RE, while pH had an opposite effect. However, BTF2 exhibited a higher specific removal capacity (SRC) due to its superior surface properties, though its performance was limited by filter bed compactation. In conclusion, BTFs using these two materials as support media demonstrate biological efficiency in methane removal, highlighting their potential for treating methane emissions from the anaerobic decomposition of organic matter in agricultural activities.